With dedication: "au vénérable frère Meuron patriarche de Locle son frère aimé M. Bakunine 1869". From: REF AN 23 - Mroczkowski, ..., (1868)
With dedication: "au vénérable frère Meuron patriarche de Locle son frère aimé M. Bakunine 1869". From: REF AN 23.